Pengembangan profesionalisme guru melalui program pendidikan berkelanjutan: Sebuah kajian literatur - Munawir Munawir; Faradisa Putri Yani; Elok Amelia Az-zahra (Indonesian Journal of Learning and Educational Studies, 2025)
Teacher professionalism development is a key factor in improving the quality of education. In line with the changing times and the dynamic needs of education, teachers are required to continuously update their knowledge, skills, and professional attitudes. This study aims to analyze various literature findings related to the development of teacher professionalism through continuous education programs. The method used in this study is a systematic literature review of scholarly articles, research reports, and relevant policy documents from the past ten years. The results show that in the context of 21st-century education, teachers are expected to adapt to diverse classroom dynamics through flexible teaching strategies that respond to students' needs. Schools play a strategic role in supporting continuous professional development (CPD) by providing training, forming learning communities, and collaborating with external institutions. In addition, Classroom Action Research (CAR) is recognized as an effective method for improving both student learning outcomes and teacher professional development. Through the implementation of these strategies, it is expected that the overall quality of education can be enhanced, better preparing the younger generation to face future challenges.